2014
DOI: 10.1089/jpm.2013.0442
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for Frontline End-of-Life Care: Exploring the Perspectives of Paramedics and Emergency Medical Technicians

Abstract: These study results suggest the need for addressing the potential interrelationship between prehospital and EOL care through improved education and protocols for care in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 12 publications
0
37
0
5
Order By: Relevance
“…Several factors influence the conveyance decision: their experience and confidence (where experience was reported as more important than training),58 61 62 64 69 72 73, previous negative experiences,52 63 gender56 and the health status of the EMS staff 62. One study that examined the influence of EMS staff gender on non-conveyance due to patient refusal found that all-male teams were 4.75 times more likely to be confronted with a refusal of medical aid and subsequent conveyance to the ED than all-female and mixed-gender teams 56…”
Section: Resultsmentioning
confidence: 99%
“…Several factors influence the conveyance decision: their experience and confidence (where experience was reported as more important than training),58 61 62 64 69 72 73, previous negative experiences,52 63 gender56 and the health status of the EMS staff 62. One study that examined the influence of EMS staff gender on non-conveyance due to patient refusal found that all-male teams were 4.75 times more likely to be confronted with a refusal of medical aid and subsequent conveyance to the ED than all-female and mixed-gender teams 56…”
Section: Resultsmentioning
confidence: 99%
“…Although only a minority of participants in each study reports these concerns, there are similarities in the kinds of challenges identified. These problems include difficulty understanding and explaining the form, 19,[24][25][26] challenges obtaining a clinician signature on forms that other members of the healthcare team prepare, 19,25,27 discomfort with problems that the form raises, 19 problems when transferring POLST across settings, 19,23,[25][26][27] family disagreements about the content, 25,27 problems with using POLST to guide treatment, 25 and inadequate education about the form for providers. 19,25 The time required to complete a POLST can also represent a barrier to use in some settings.…”
Section: Healthcare Provider Attitudes Toward and Experiences With Polstmentioning
confidence: 99%
“…[13][14][15][16]19 Code status is not predictive of a patient's preferences for other kinds of treatments, 14,16,19 highlighting the limitations of relying on code status alone to guide treatment decisions. 36 Healthcare providers largely hold positive views of POLST and find it useful in guiding discussions and decisions about treatments, but there are numerous challenges associated with use of the tool, ranging from challenges understanding and explaining the form 19,[24][25][26] to logistical challenges such as problems transferring the form across settings. 19,23,[25][26][27] Although only a minority of respondents identified these problems, the concerns raised suggest the need for systems-focused quality improvement efforts.…”
Section: Summary Of Polst Researchmentioning
confidence: 99%
“…NYS recognizes advance directives (NYS Health Care Proxy Form and NYS Living Will) and medical orders (Non‐hospital Do Not Resuscitate [DNR] Order and MOLST) for the documentation of end‐of‐life wishes. In a prior study, the MOLST was favourably endorsed by EMS providers for facilitating rapid decision making in the moments before death (Waldrop et al., ). In the absence of documented orders to the contrary, patients typically receive the most aggressive treatment possible (Bigby, Bowers, & Webber, ; IOM, ).…”
Section: Introductionmentioning
confidence: 99%